PSYCHOANALYTIC INTERPRETATION OF JUSTICE IN CONTEXT OF TECHNO-GENESIS PROBLEMS (Part I) - N. I. Mushinskij (Наука и техника)
Problem of Justice takes a great significance in the context of the processes of techno-genesis. Ethics of psychoanalysis connects a category of Justice with the notion of Unconscious. A psychoanalytic methodology of Freud helps successfully to solve modern technogenic problems.